Pengaruh Kombinasi Bisnis Pt. Bank Syariah Indonesia (Bsi) Tbk Terhadap Perkembangan Ekonomi Syariah Di Indonesia - Dinda Kusumaningrum; Putri Anggita Sari; Ariella Yoharin Panjaitan; Endang Kartini Panggiarti (Pusat Riset dan Inovasi Nasional, 2024)
Considering the importance of economic activities in maintaining national stability, sharia banking is considered as an approach to boosting the nation's economy. Bank Rakyat Indonesia Syariah (BRIS), Bank Negara Indonesia Syariah (BNIS), and Bank Syariah Mandiri (BSM), three sharia banks that were previously in existence, have merged as a result of the growth of the sharia banking sector in Indonesia, into one business entity. The process of merging two companies into one, where one takes a new name and the other is dissolved while all its assets are combined into the still operating business, is known as a merger. Of course, mergers are carried out with a specific purpose, as is currently experienced by the banking industry. In the context of these concerns, researchers plan to explore the impact of the consolidation of three state-owned sharia banks on the development of Indonesia's sharia economy. The influence of PT business combinations is revealed through the use of a literature observation approach in this research. Indonesia's sharia economic growth will be considered with a focus on Bank Syariah Indonesia (BSI) Tbk. Secondary data for this research was obtained from various sources, including scientific journals, e-books, and other relevant sources. This research aims to investigate the influence of the Indonesian Sharia Bank (BSI) business combination on the development of the sharia economy in these countries